Costimulation Signals for Memory CD8+ T Cells During Viral Infections - Priyanka Duttagupta; Alina C. Boesteanu; Peter D. Katsikis (2009)
Costimulation signals have been recognized as critical for optimal T-cell responses and result from important interactions between receptors on the surface of T cells and their ligands on antigen-presenting cells. Two families of receptors, the CD28 family and the tumor necrosis factor receptor (TNFR) family, have been found to be major players in providing costimulation to CD8+ T cells. Recent studies using viral infection models have highlighted the importance of CD28 costimulation signals during memory responses against viruses. Programmed death-1 (PD-1), another member of the CD28 family, may contribute to functional defects of helpless memory CD8+ T cells. Members of the TNFR family, such as CD27, 4-1BB, CD40, TRAIL (tumor necrosis factor-related apoptosis-inducing ligand), and OX40, have also been implicated in the survival, generation, maintenance, and quality of virus-specific memory CD8+T cells. The delivery of costimulatory molecules such as CD28, 4-1BB, and OX40 can help boost the generation and function of virus-specific memory CD8+ T cells. The use of costimulatory molecules as adjuvants, along with viral antigens in vaccines, may facilitate the generation of effective antigen-specific memory CD8+ T-cell responses. Understanding the costimulatory requirements of memory CD8+ T cells, therefore, may lead to improved vaccines that target anti-viral CD8+ T-cell memory.